Detection and characterization Salmonella enterica from broiler chicken(Rose308) in Thi-Qar province and its relationship to broiler immunity and body weight - Hassan Ghargan, Noor; Abdulkareem, Ali A.; Kareem Hanan, Zaman (University of Thi-Qar Journal of agricultural research, 2023)
This study was conducted to isolate Salmonella bacteria from broiler (ROSS 308). A total of 184 stool samples were collected from chickens, showed symptoms of infection with salmonella bacteria from two different fields in Thi-Qar Governorate in Al-Islah district and Al-Fadeliyah district. Thirty isolates (16.2%) were diagnosed with Salmonella infection by biochemical and API 20 E tests. The pathological infection was confirmed in chickens by analyzing the level of antibodies in the blood of chickens, there was an increase in the level of immunoglobulin IgG and IgM, confirmed the existence of the disease and the stage of infection between a new infection and the acquisition of immunity, as a result of the previous injury and injuries close to recovery. The birds that suffer from a lack of weight differed in the stage of infection, this indicates that infection at any stage has a significant impact on the weights of birds infected with salmonella bacteria.